Antifungal activity of five chemical and two biological fungicides for the management of Botrytis cinerea, causal agent of Gray Mold in Strawberry - Llanos, A. (2018)
Gray mold, caused by Botrytis cinerea, is one of the most important plant diseases in Strawberry in Peru. Because of its high variability and its pathogenic characteristics, proper fungicides use is essential to control this disease. The aim of this study was to evaluate the effect of five chemical fungicides: Tryfloxistrobin (0.0625%), Pyrimethanil + Fluopyram (0.1%), Pyrimethanil (0.1%), Fenhexamid (0.135%) and Carbendazim (0.125%), and two biological fungicides: Bacillus subtilis QST713 (0.75%) and Bacillus pumilus QST2808 (0.75%) in laboratory and field conditions. In the laboratory phase, the inhibition of mycelial growth was measured by evaluating diameter growth at 4 DAI (p≤0.05). Furthermore, conidial germination inhibition was evaluated in two different ways. First, one hundred conidia were placed in sterile water with fungicide and evaluated at 24 HAI (p≤0.05). Second, the number of CFUs was counted in poisoned PDA medium at 3 DDI. The doses 1x106 and 125 conidia/mL were used for each test respectively. The field experiment was in Aucallama, Huaral. Chemical and biological fungicides were sprayed in a strawberry cultivar Aromas. Twelve harvests were done. The results showed that chemical fungicides; Trifloxystrobin, Pyrimethanil + Fluopyram, Pyrimethanil, Fenhexamid and the biological fungicide Bacillus subtilis QST713 had considerable activity against Botrytis cinerea in most of the variables assessed. These results will contribute to the evaluation of the potential of each one of these fungicides for the management of Botrytis cinerea.